American Catholics and the Quest for Equality in the Civil War Era - Curran, Robert Emmett (Book collections on Project MUSE., 2023)
"Emmett Curran's masterful treatment of American Catholicism in the Civil War era is the first comprehensive history of the denomination in the North and South before, during, and after the war. It is the story of how the momentous developments of these decades impacted the Catholic community and how Catholics contributed to the reshaping of a nation that survived the greatest threat to its preservation that it has ever faced. It is also a significant part of the story of how the revolution that the war touched off remained unfinished, indeed was turned backward, in no small part by Catholics whose pursuit of "equality" was marred by a truncated vision of who deserved to share in its realization. Throughout early American history, most Protestants considered Catholics to be internal aliens, incapable of becoming full citizens because faith trumped nationality in determining their ultimate allegiance. By the mid-nineteenth century, conversions and immigration threatened to make them the nation's largest Christian denomination, a prospect particularly alarming to evangelical Protestants. By the late 1840s, most Catholics were foreign-born urban dwellers in the North. That startling demographic change revitalized a nativism that became a major political force, in large part by depicting Catholics as a danger to the republic. In the political realignment of the 1850s over immigration and slavery, Catholics became the backbone of the northern wing of a Democratic Party committed to both. During the Civil War, Catholics on both sides took pride in their transnational religious allegiance, a bond transcending sectional conflict. Most Catholics also shared a commitment to slavery. Northern Catholics initially supported the war since its goal was to preserve the Union, not abolish slavery. Catholics in the border states became part of the minority favoring the Confederacy, but for many northern Catholics, Lincoln's emancipation proclamation, in violating the property protections that the Constitution provided, delegitimized the war. In the press, in secret organizations, and in the streets, Catholics increasingly denounced the centralization of power and suppression of civil liberties to which the Lincoln administration resorted. Resistance to the war by Catholics became increasingly violent, culminating in the New York City riot of July 1863. Catholics became vital members of the Sons of Liberty and other organizations which sought to force a peace settlement by whatever means necessary. They were also part of the conspiracy to kidnap President Lincoln, which morphed into the president's assassination. That complicity exacerbated charges of disloyalty that Catholic resistance to the war had stirred over its latter course. Still, Catholics expected to secure, from their war service, an unprecedented equality of place among their fellow citizens, part of the "new birth of freedom" that Lincoln had proclaimed at Gettysburg. A racially restrictive vision of the American promise led Catholics to approach Reconstruction as a restoration of the old order. Catholics, particularly in Virginia and Louisiana, played key roles in "redeeming" the South from Republican governments. Catholics were prominent in the creation and promotion of Lost Cause mythology, which largely curtailed the pursuit of equality that had been a core part of the nation's mission since its inception. Catholics had known for generations the consequences of being treated inequitably. Nevertheless, when the moment came to be part of a revolution to right this historic imbalance for everyone, most white Catholics could not rise above their tribal interests to treat equality as something more than a zero-sum commodity"--